Reflection-type mask blank and method for manufacturing reflection-type mask

By using a multi-layer reflective film, Ru protective film and Ta-N absorbing film in the reflective mask blank, and ensuring that the nitrogen content of the absorbing film reaches more than 30 atm%, the problem that it is difficult to maintain a good cross-sectional shape of the absorbing film when improving the contrast in the prior art is solved, and a combination of high contrast and good cross-sectional shape is achieved.

CN119902409APending Publication Date: 2025-04-29SHIN ETSU CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411465764.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-27
Filing Date
2024-10-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

While improving the contrast of pattern inspection light, the conventional reflective mask blank is difficult to maintain good cross-sectional shape of the absorbing film, resulting in the pattern shape being easily deteriorated.

Method used

By forming a multi-layer reflective film, a protective film containing Ru and an EUV mask blank of absorbing film composed of Ta and N on the substrate, a single-layer film containing 30 atm% or more is used to ensure that the reflectivity contrast of pattern inspection light is maintained at more than 20%, thereby improving the cross-sectional shape of the absorbing film.

Benefits of technology

It is achieved to ensure that the cross-sectional shape of the absorbent film is good while maintaining a high contrast, thereby improving the shape quality of the pattern.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119902409A_ABST
    Figure CN119902409A_ABST
Patent Text Reader

Abstract

The reflective mask blank according to the present invention is used as a raw material for a reflective mask used in EUV lithography using EUV light as exposure light, and is characterized by comprising: a substrate 10; a multilayer reflective film (20) that is formed on one main surface of the substrate (10) and reflects exposure light; a protective film (50) formed in contact with the multilayer reflective film (20); and an absorbing film (70) for absorbing exposure light formed on the protective film (50). The protective film (50) is formed from a film containing ruthenium (Ru). The absorber film (70) is formed of a single-layer film comprising tantalum (Ta) and nitrogen (n), the nitrogen content being 30 at% or more and less than 60 at%. The contrast between the reflected light on the surface of the protective film 50 and the reflected light on the surface of the absorbing film 70 is 20% or more with respect to light having a wavelength of 193 nm to 248 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a reflective mask blank as a material of a reflective mask used for manufacturing semiconductor devices such as LSI, and a method of manufacturing a reflective mask from the reflective mask blank. Background Art

[0002] In the manufacturing process of semiconductor devices (semiconductor apparatuses), photolithography technology is widely used to repeatedly irradiate a transfer mask with exposure light and transfer the circuit pattern formed on the mask to a semiconductor substrate (semiconductor wafer) through a reduced projection optical system. In the past, the wavelength of exposure light was mainly 193nm using argon fluoride (ArF) excimer laser, and by adopting a process called multi-patterning that combines multiple exposure processes and processing processes, a pattern with a size smaller than the exposure wavelength was finally formed.

[0003] However, as the industry continues to demand the miniaturization of device patterns, it is necessary to form further fine patterns. Therefore, as exposure light, EUV lithography technology that uses extreme ultraviolet (hereinafter referred to as "EUV") light with a shorter wavelength than ArF excimer laser is increasingly recognized by the industry. EUV light refers to light with a wavelength of about 0.2 to 100nm, more specifically, light with a wavelength of around 13.5nm. EUV light has extremely low transmittance to matter, and the previous transmission-type projection optical system and mask cannot be used, so reflective optical elements are used. Therefore, reflective masks are also proposed as masks for pattern transfer.

[0004] A reflective mask is formed by forming a multilayer reflective film that reflects EUV light on a substrate, and forming an absorption film pattern that absorbs EUV light on the multilayer reflective film. On the other hand, the absorption film in a state before patterning the absorption film (including the absorption film in a state where a resist film is formed) is called a reflective mask blank, which is used as a material for a reflective mask. A reflective mask blank generally has a basic structure including a substrate with low thermal expansion, a multilayer reflective film that reflects EUV light formed on one of the two main surfaces of the substrate, and an absorption film that absorbs EUV light formed thereon.

[0005] As a multilayer reflective film, a multilayer reflective film having a necessary reflectivity for EUV light by alternately stacking molybdenum (Mo) layers and silicon (Si) layers is generally used. On the other hand, as an absorption film, tantalum (Ta) or the like having a relatively large extinction coefficient for EUV light is used (Japanese Patent Publication No. 2002-246299).

[0006] In addition, as a protective film (cover film) for protecting the multilayer reflective film, a ruthenium (Ru) film disclosed in Japanese Patent Publication No. 2002-122981 is formed on the multilayer reflective film. In addition, as an etching mask when forming a pattern on the absorption film, there is also a case where an etching mask film containing chromium (Cr) is formed on the absorption film. On the other hand, a back conductive film is formed on the other main surface of the substrate. As the back conductive film, a metal nitride film is proposed for electrostatic adsorption, and films mainly containing chromium (Cr) and tantalum (Ta) can be listed.

[0007] The reflective mask can form a pattern on the absorption film, absorb EUV light in a certain part of the absorber pattern, and reflect EUV light in other exposed protective film parts, thereby being used as a mask for photolithography.

[0008] After forming a pattern on the absorption film, an inspection is performed to determine whether the absorber pattern is formed as designed. Light with a wavelength of about 190nm to 260nm is used as a mask to perform pattern inspection of the reflected image of the light.

[0009] Therefore, in the pattern inspection of the absorption film, the contrast between the reflected light of the absorption film and the reflected light of the portion where the absorption film is removed and the protective film is exposed with respect to the inspection light becomes important.

[0010] In order to improve the contrast, it is effective to form an oxide layer as a reflectivity-reducing layer on the surface of the absorption film. By intentionally forming a film with a high oxygen content, the reflectivity to the inspection light can be reduced and the reflectivity contrast can be improved. However, when a film with a high oxygen content is formed on the surface, the etching rate of the oxide film during etching during processing is slower than that of the oxygen-free layer on the substrate side of the reflectivity-reducing layer of the absorption film, and there is a problem that the cross-sectional shape of the formed pattern is easily deteriorated.

[0011] An object of the present invention is to provide a reflective mask blank capable of producing a reflective mask having a high contrast and a good cross-sectional shape of an absorption film, and a method for producing a reflective mask using the reflective mask blank.

[0012] The present invention was completed in order to solve the above-mentioned problems. The inventor discovered that in an EUV mask blank in which a multilayer reflective film, a protective film containing Ru, and an absorption film composed of Ta and N are sequentially formed on a substrate, by making the absorption film a single-layer film containing more than 30atm% of nitrogen, the cross-sectional shape of the pattern formed is improved while the contrast of the reflectivity of the pattern inspection light is maintained at more than 20%, thereby completing the present invention.

[0013] Therefore, the present invention provides the following reflective mask blank and method for manufacturing a reflective mask. Summary of the invention

[0014]

Concept 1

[0015] The reflective mask blank of the present invention is used as a raw material of a reflective mask used in EUV lithography using EUV light as exposure light, and is characterized by comprising:

[0016] substrate;

[0017] a multilayer reflective film formed on one main surface of the substrate and used for reflecting exposure light;

[0018] a protective film formed in contact with the multilayer reflective film; and

[0019] an absorbing film that absorbs exposure light formed on the protective film,

[0020] wherein the protective film is formed of a film containing ruthenium (Ru),

[0021] The absorption film is formed of a single layer film composed of tantalum (Ta) and nitrogen (N), wherein the content of nitrogen is greater than 30 atomic % and less than 60 atomic %.

[0022] The contrast ratio between the reflected light on the surface of the protective film and the reflected light on the surface of the absorption film with respect to light having a wavelength of 193 nm to 248 nm is 20% or more.

[0023]

Concept 2

[0024] In the reflective mask blank based on Concept 1,

[0025] The absorption film has a thickness of 50 nm to 80 nm.

[0026]

Concept 3

[0027] In a reflective mask blank based on Concept 1 or 2,

[0028] The protective film is composed of ruthenium (Ru) or ruthenium (Ru) and niobium (Nb).

[0029]

Concept 4

[0030] In the reflective mask blank according to any one of Concepts 1 to 3,

[0031] The protective film has a thickness of 2 nm to 5 nm.

[0032]

Concept 5

[0033] In the reflective mask blank according to any one of Concepts 1 to 4,

[0034] The invention further comprises: an etching mask film containing Cr, wherein the Cr is used as an etching mask when processing the absorption film.

[0035]

Concept 6

[0036] The reflective mask blank according to claim 1 or 2 can be produced by sputtering film formation.

[0037]

Concept 7

[0038] In the method for manufacturing a reflective mask blank according to concept 6,

[0039] After forming the absorption film on the surface away from the substrate, the surface may be exposed to air or subjected to heat treatment at a temperature of 150° C. or less in the air atmosphere to form an oxide layer with a thickness of 2 nm or less.

[0040] Concept 8

[0041] In the method for manufacturing a reflective mask blank according to concept 6 or 7,

[0042] The protective film is composed of ruthenium (Ru) or ruthenium (Ru) and niobium (Nb), and after the protective film is formed, heat treatment is performed at 150° C. or less in an air atmosphere.

[0043] Effects of the Invention

[0044] According to the present invention, it is possible to provide a reflective mask blank capable of producing a reflective mask having an absorption film with a good cross-sectional shape while achieving high contrast. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a longitudinal cross-sectional view of an example of a reflective mask blank according to an embodiment of the present invention.

[0046] Figure 2 This is a longitudinal sectional view showing a state in which a pattern of an absorption film is formed on a reflective mask blank according to an embodiment of the present invention.

[0047] Figure 3 This is a longitudinal sectional view showing a state in which an etching mask film is provided in a reflective mask substrate according to an embodiment of the present invention.

[0048] Figure 4 This is a longitudinal sectional view showing a state in which an etching mask film and a resist film are provided on a reflective mask blank according to an embodiment of the present invention.

[0049] Figure 5 It is a longitudinal sectional view showing a mode of forming a pattern of an etching mask film using a resist pattern as an etching mask in a reflective mask substrate according to an embodiment of the present invention. DETAILED DESCRIPTION

[0050] Hereinafter, embodiments of the present invention will be described in more detail.

[0051] like Figure 1As shown, the reflective mask blank of this embodiment includes a multilayer reflective film 20 for reflecting exposure light formed on one main surface (surface) of a substrate 10, a protective film 50, and an absorption film 70, and may further include an etching mask film 170 that functions as an etching mask when processing the absorption film 70 (see Figure 3 and Figure 4 ). In addition, a back conductive film 30 may be provided on the other main surface of the substrate.

[0052] Reflective mask blanks are suitable as materials for reflective masks used in EUV lithography using EUV light as exposure light. The wavelength of EUV light used in EUV lithography using EUV light as exposure light is 13 to 14 nm, usually around 13.5 nm. Reflective mask blanks and reflective masks using EUV light as exposure light are also called EUV mask blanks and EUV masks, respectively.

[0053] The substrate 10 is preferably used for EUV light exposure and has low thermal expansion characteristics. For example, the thermal expansion coefficient is preferably within ±2×10 -8 / ℃, preferably within ±5×10 -9 / ℃ or less. Examples of such materials include titanium dioxide-doped quartz glass (SiO 2 -TiO 2 System glass) etc. In addition, the substrate 10 preferably uses a substrate with a fully flat surface, and the surface roughness of the main surface of the substrate 10 is preferably 0.5nm or less, more preferably 0.2nm or less in RMS value. Such surface roughness can be obtained by grinding the substrate 10, etc. The size of the substrate 10 is preferably that the size of the main surface of the substrate 10 is 152mm square, and the thickness of the substrate 10 is 6.35mm. The substrate 10 of this size is a so-called 6025 substrate (a substrate having a main surface size of 6 inches square and a thickness of 0.25 inches).

[0054] The multilayer reflective film 20 is a film that reflects exposure light in a reflective mask. The multilayer reflective film 20 is preferably provided in contact with one main surface of the substrate 10, but another film such as a base film may be provided between the multilayer reflective film 20 and one main surface of the substrate 10. The multilayer reflective film 20 has a periodic stacked structure in which high refractive index layers with a relatively high refractive index to exposure light and low refractive index layers with a relatively low refractive index to exposure light are alternately stacked.

[0055] The high refractive index layer is preferably formed by a material containing silicon (Si). The high refractive index layer can contain more than one additive element selected from oxygen (O), nitrogen (N), carbon (C), boron (B) and hydrogen (H), and can also be composed of a layer containing the additive element and a multilayer layer that does not contain the additive element. The thickness of the high refractive index layer is preferably more than 3.5NM, more preferably more than 4NM, in addition, preferably less than 4.9NM, more preferably less than 4.4NM.

[0056] Low refractive index layer is preferably formed by the material that does not contain molybdenum (MO). In addition, low refractive index layer can also be formed by the material that contains ruthenium (RU). Low refractive index layer can contain more than one additive element selected from oxygen (O), nitrogen (N), carbon (C), boron (B) and hydrogen (H), and can also be composed of the multilayer of the layer that contains the additive element and does not contain the additive element. The thickness of low refractive index layer is preferably more than 2.1nm, more preferably more than 2.6nm, in addition, preferably below 3.5nm, more preferably below 3nm.

[0057] As long as the periodic stacking structure comprises a high refractive index layer and a low refractive index layer, one period comprises more than 1 layer of high refractive index layer and more than 1 layer of low refractive index layer. The number of plies included in the periodic stacking structure is more than 2 layers, and the periodic stacking structure, for example, can include a high refractive index layer and a low refractive index layer. In addition, it is also possible to contain more than 2 layers of high refractive index layers whose compositions are different from each other (for example, composition ratio is different, according to the presence or absence of added elements, etc.), and contain more than 2 layers of low refractive index layers whose compositions are different from each other (for example, composition ratio is different, according to the presence or absence of added elements, etc.). In this case, the number of plies included in the periodic stacking structure is more than 3 layers, can be more than 4 layers or more than 5 layers, but is preferably less than 8 layers. The number of periods is preferably more than 30 periods, and is preferably less than 50 periods, more preferably less than 40 periods. In the case where the low refractive index layer is formed by the material containing ruthenium (Ru), the layer (uppermost layer) farthest from substrate 10 in the periodic stacking structure is preferably a high refractive index layer.

[0058] The thickness of the multilayer reflective film 20 having a periodic stacking structure is adjusted according to the exposure wavelength and the incident angle of the exposure light, and is preferably 200 nm or more, more preferably 270 nm or more, and is preferably 400 nm or less, more preferably 290 nm or less.

[0059] As a method for forming the multilayer reflective film 20, a sputtering method in which power is supplied to a target and the atmospheric gas is plasmatized (ionized) with the supplied power to perform sputtering, and an ion beam sputtering method in which an ion beam is irradiated onto a target. As a sputtering method, there is a DC sputtering method in which a direct current voltage is applied to a target, and an RF sputtering method in which a high-frequency voltage is applied to a target. The sputtering method is a film-forming method in which a voltage is applied to a target in a state where a sputtering gas is introduced into a chamber to ionize the gas and utilize the gas ion sputtering phenomenon. In particular, the magnetron sputtering method is advantageous in terms of productivity. The power applied to the target may be DC or RF, and DC includes pulse sputtering, which reverses the negative bias applied to the target for a short time to prevent the target from being charged.

[0060] The multilayer reflective film 20 can be formed by a sputtering method using, for example, a sputtering device capable of mounting a plurality of targets. Specifically, as a target, the multilayer reflective film 20 can be appropriately selected from: a molybdenum (Mo) target for forming a layer containing molybdenum (Mo), a ruthenium (Ru) target for forming a layer containing ruthenium (Ru), a silicon (Si) target for forming a layer containing silicon (Si), etc., and as a sputtering gas, a rare gas such as helium (He) gas, argon (Ar) gas, krypton (Kr) gas, and xenon (Xe) gas can be used.

[0061] In addition, in the case of reactive sputtering using a reactive gas, for example, when forming a nitrogen (N)-containing film, a nitrogen-containing gas such as nitrogen (N2) gas can be used; when forming an oxygen (O)-containing film, an oxygen-containing gas such as oxygen (O) can be used. 2 ) gas; when forming a film containing nitrogen (N) and oxygen (O), nitrous oxide (N 2 O) gas, nitric oxide (NO) gas, nitrogen dioxide (NO 2 ) gas, and when forming a film containing carbon (C) and oxygen (O), carbon monoxide (CO) gas can be used; when forming carbon dioxide (CO 2 ) gas, such as carbon dioxide gas, or hydrogen (H) containing membranes, you can use hydrogen (H 2 ) gas or other hydrogen-containing gases; when forming a film containing carbon (C) and hydrogen (H), methane (CH 4 ) gas and other hydrocarbon gases, and can be used together with rare gases.

[0062] When forming a layer containing boron (B), a molybdenum (Mo) target to which boron (B) is added (molybdenum boride (MoB) target), a silicon (Si) target to which boron (B) is added (silicon boride (SiB) target), or the like can be used.

[0063] The protective film 50 is also called a capping film. The protective film 50 is used to protect the multilayer reflective film 20. The protective film 50 is usually provided in contact with the multilayer reflective film 20. The protective film 50 is formed of a material containing ruthenium (Ru).

[0064] As materials containing ruthenium (Ru), there can be mentioned ruthenium (Ru) alone, alloys consisting of ruthenium (Ru) and metals or semimetals different from ruthenium (Ru), etc. As metals or semimetals different from ruthenium (Ru), there can be mentioned niobium (Nb), rhenium (Re), zirconium (Zr), titanium (Ti), chromium (Cr), silicon (Si), etc. The content of metals or semimetals different from ruthenium (Ru) in the protective film 50 is preferably 30 atomic % or less, and more preferably 20 atomic % or less. The lower limit of the content of metals or semimetals different from ruthenium (Ru) in the protective film 50 is not particularly limited, but is preferably 5 atomic % or more, and more preferably 10 atomic % or more.

[0065] The protective film 50 may be a single-layer structure or a multi-layer structure in which a plurality of layers having different compositions are combined. In addition, each layer constituting the single layer or the plurality of layers may have a gradient composition structure in which the composition changes continuously in the thickness direction. In particular, one or both of the side of the protective film 50 closest to the multilayer reflective film 20 (in the case of a multilayer structure, the layer closest to the multilayer reflective film 20) and the side farthest from the multilayer reflective film 20 (in the case of a multilayer structure, the layer farthest from the multilayer reflective film 20) may be made of ruthenium (Ru).

[0066] In addition, when the protective film 50 has a multilayer structure or a gradient composition structure, it is preferable that the content of the metal or semimetal different from ruthenium (Ru) gradually increases from the multilayer reflective film side to the side away from the multilayer reflective film in a part or all of the thickness direction of the protective film 50. In particular, when niobium (Nb) is contained as the metal or semimetal different from ruthenium (Ru), since the inclusion of niobium (Nb) is also effective in improving the resistance to dry etching using a gas containing chlorine (Cl) and oxygen (O), it is preferable that the content of niobium (Nb) gradually increases from the multilayer reflective film side to the side away from the multilayer reflective film in a part or all of the thickness direction of the protective film 50.

[0067] In addition, in this embodiment, as dry etching using a gas containing chlorine (Cl) and oxygen (O), specifically, dry etching using a gas containing chlorine (Cl2) gas and oxygen (O2) gas can be cited. The gas containing chlorine (Cl) and oxygen (O) may also contain rare gases such as helium (He) gas, argon (Ar) gas, krypton (Kr) gas, and xenon (Xe) gas.

[0068] The thickness of the protective film 50 is preferably 2 nm or more, more preferably 3 nm or more, and preferably 5 nm or less, more preferably 4 nm or less. When the thickness of the protective film 50 is less than 2 nm, the function of protecting the multilayer reflective film becomes insufficient, and when the thickness exceeds 5 nm, the reflectivity of EUV light decreases.

[0069] The protective film 50 can be appropriately selected as a target from: a ruthenium (Ru) target, a target of a metal or semimetal different from ruthenium (Ru), specifically, a niobium (Nb) target, a rhenium (Re) target, a zirconium (Zr) target, a titanium (Ti) target, a chromium (Cr) target, a silicon (Si) target, a target mixed with two or more selected from niobium (Nb), rhenium (Re), zirconium (Zr), titanium (Ti), chromium (Cr) and silicon (Si), and a target mixed with ruthenium (Ru) and one or more of niobium (Nb), rhenium (Re), zirconium (Zr), titanium (Ti), chromium (Cr) and silicon (Si) The target of the metal or semimetal different from ruthenium (Ru) can be appropriately selected and used, and as a sputtering gas, a rare gas such as helium (He) gas, argon (Ar) gas, krypton (Kr) gas, and xenon (Xe) gas can be used for sputtering. Sputtering is preferably magnetron sputtering.

[0070] The multilayer reflective film 20 or the protective film 50 may be heat-treated after being formed. By heat-treating, it is possible to suppress the change in characteristics such as reflectivity of EUV light when heat is generated during the formation of the mask pattern. The heat treatment temperature is generally preferably 120° C. to 150° C. If the temperature is higher than 150° C., the reflectivity of EUV light decreases, which is not preferred.

[0071] Heat treatment may be performed after the formation of the multilayer reflective film 20 or the protective film 50 or both. However, from the perspective of concerns about defect adhesion and productivity, the number of heat treatments is preferably reduced, and heat treatment is preferably performed after the formation of the protective film 50.

[0072] On the other hand, when heat treatment is performed after the protective film 50 is formed, an oxide film may be formed on the surface of the protective film 50, and the reflectivity of the pattern inspection light may be reduced. In addition, even if heat treatment is not performed after the protective film 50 is formed, it is entirely possible that the surface layer of the protective film 50 is oxidized after the pattern is formed, so the reflectivity of the absorption film 70 to the pattern inspection light needs to be set to a reflectivity based on the premise that the protective film 50 is oxidized.

[0073] The absorption film 70 is a single-layer structure composed of Ta and n. After the absorption film 70 is formed, a natural oxide layer may be formed by exposing the absorption film 70 to the atmosphere. In addition, after the absorption film 70 is formed, a heat treatment at 150°C may be performed for the purpose of adjusting the film stress, etc., and an oxide film may be formed by the heat treatment. At this time, it is preferred that the oxide film formed on the surface is as thin as possible, less than 2 nm, and more preferably less than 1 nm. In the case where the oxide film on the surface is formed thicker, the etching speed of the oxide film is slower than that of the unoxidized layer, which may lead to deterioration of the pattern shape, and is therefore not preferred.

[0074] The absorption film 70 preferably contains nitrogen in an amount of 30% to 60%, and more preferably 40% to 55%. When the nitrogen content is less than 30%, the reflected light of the pattern inspection light becomes too high, and the reflectivity and contrast become low. On the other hand, when the nitrogen content is higher than 60%, EUV light is difficult to absorb, and the sheet resistance of the absorption film 70 becomes too high, so it is not preferred.

[0075] In addition, the definition of contrast is as follows.

[0076] Contrast (%) = ((Rc) - (Ra)) / (Rc + Ra)) × 100

[0077] Rc: reflectivity of the protective film 50 to the inspection light

[0078] Ra: reflectivity of the absorption film 70 to the inspection light

[0079] The contrast of the pattern inspection light is preferably high. Specifically, the contrast is preferably 20% or more, more preferably 25% or more. When the contrast is 15% or less, the edge of the pattern cannot be detected, and the possibility of failing to detect an abnormal position becomes high.

[0080] The film thickness of the absorption film 70 containing Ta is preferably 50 nm to 80 nm in total for all layers, and more preferably 55 nm to 70 nm. The thin film resistance of the absorption film 70 is preferably 10^6Ω / □ or less, and more preferably 10^5Ω / □ or less. The surface roughness Sq of the absorption film 70 is preferably 0.8 nm or less, and more preferably 0.6 nm or less. This is because, when the absorption film 70 formed by a single-layer film composed of tantalum (Ta) and nitrogen (N) is less than 50 nm, the reflectivity of the absorber film portion to EUV light is not sufficiently reduced during mask production, and the contrast with the opening portion cannot be fully obtained. When it exceeds 80 nm, the wafer transfer performance deteriorates due to the influence of the three-dimensional effect during exposure.

[0081] The absorption film 70 can be formed by sputtering, and the sputtering is preferably magnetron sputtering. A tantalum (Ta) target or a target containing tantalum (Ta) and nitrogen (N) can be used, and a rare gas such as helium (He) gas, neon (Ne) gas, argon (Ar) gas, krypton (Kr) gas, or xenon (Xe) gas can be used as a sputtering gas. In addition, a rare gas and nitrogen (N 2 ) gas by reactive sputtering to form the absorption film 70.

[0082] like Figure 3As shown, on the side of the absorption film 70 away from the substrate 10, an etching mask film 170 as the absorption film 70 may be provided, and the etching mask film 170 having etching characteristics different from those of the absorption film 70. The etching mask 170 is a film used as an etching mask when the absorption film 70 is dry-etched. Preferably, the etching mask film 170 is provided in contact with the absorption film 70. The etching mask film 170 may be a single layer or a multilayer. As the etching mask film 170, a film containing Cr is preferred, and CrN, CrO, CrON, CrCON, etc. may be listed. The thickness of the etching mask film 170 is not particularly limited, but if it is too thin, it may not function as an etching mask. In addition, if it is too thick, the processing characteristics may deteriorate. Therefore, it is preferably 1 nm or more, more preferably 2 nm or more, and further preferably 5 nm or more, and preferably 20 nm or less, and more preferably 10 nm or less.

[0083] The etching mask film 170 can be formed by sputtering. Specifically, when the etching mask film 170 is formed of a material containing chromium (Cr), a chromium (Cr) target or a chromium (Cr) compound target (a target containing chromium (Cr) and oxygen (O), nitrogen (N), carbon (C), etc.) can be used. When the etching mask film 170 is formed of a material containing tantalum (Ta), a tantalum (Ta) target or a tantalum (Ta) compound target (tantalum (Ta), oxygen (O), nitrogen (N), carbon (C), boron (B) can be appropriately selected according to the composition. As a sputtering gas, a rare gas such as helium (He) gas, argon (Ar) gas, krypton (Kr) gas, and xenon (Xe) gas can be used. In addition, while using a rare gas, an oxygen-containing gas, a nitrogen-containing gas, and a carbon-containing gas can also be used. Specifically, oxygen (O 2 ) gas, nitrogen (N 2 ) gas, nitrogen oxides (N 2 O, NO, NO 2 ) gas, carbon dioxide (CO, CO 2 ) gas, hydrogen (H 2 ) gases, hydrocarbon gases (e.g., methane CH 4 ) gas etc.) by reactive sputtering. Sputtering is preferably magnetron sputtering.

[0084] On the other main surface (back surface) of the substrate 10 opposite to one main surface, a conductive film (back surface conductive film 30) for electrostatically chuck- ing the reflective mask to an exposure device (eg, EUV scanner) is preferably provided close to the other main surface.

[0085] The back conductive film 30 preferably has a sheet resistance of less than 100Ω / □, and there is no particular restriction on the material. Examples of the material of the back conductive film 30 include materials containing tantalum (Ta) or chromium (Cr). In addition, the material containing tantalum (Ta) may also contain oxygen (O), nitrogen (N), carbon (C), boron (B), etc., and the material containing chromium (Cr) may also contain oxygen (O), nitrogen (N), carbon (C). As materials containing tantalum (Ta), Ta simple substance, TaO, TaN, TaON, TaC, TaCN, TaCO, TaCON, TaB, TaOB, TaNB, TaONB, TaCB, TaCNB, TaCOB, TaCONB and other tantalum (Ta) compounds can be cited. As materials containing chromium (Cr), specific examples include Cr simple substance, CrO, CrN, CrON, CrC, CrCN, CrCO, CrCON and other chromium (Cr) compounds.

[0086] The thickness of the back conductive film 30 is not particularly limited as long as it functions as an electrostatic chuck, and is generally about 20 to 300 nm. The thickness of the back conductive film 30 is preferably after forming a reflective mask, that is, after forming the pattern of the absorption film 70 (see Figure 2 ), the film stress is balanced with the film formed on one main surface (surface) side and the pattern of the film. The back conductive film 30 may be formed before forming the multilayer reflective film 20, or may be formed after forming all the films on the multilayer reflective film side of the substrate 10. Alternatively, the back conductive film 30 may be formed after forming a portion of the films on the multilayer reflective film side of the substrate 10, and then the remaining films on the multilayer reflective film side of the substrate 10 may be formed. The back conductive film 30 may be formed, for example, by magnetron sputtering.

[0087] like Figure 4 As shown, the reflective mask blank may form a resist film 190 on the side farthest from the substrate 10. The resist film 190 is preferably an electron beam (EB) resist.

[0088] From the reflective mask blank, for example, a reflective mask having a substrate 10, a multilayer reflective film 20 formed on one main surface of the substrate 10, a protective film 50 formed in contact with the multilayer reflective film 20, and a pattern of an absorbent film 70 (absorbent film pattern) can be manufactured. In the reflective mask, a transfer pattern is formed by a reflectivity difference between a portion where the absorbent film 70 is formed and a portion where the absorbent film 70 is not formed.

[0089] Reflective masks can be made by including:

[0090] Preparing a reflective mask blank process;

[0091] If necessary, a resist film 190 is formed on the absorption film 70;

[0092] A step of forming a resist pattern from the resist film 190 on the absorption film 70;

[0093] A step of etching the absorption film 70 using the resist pattern as an etching mask to form a pattern of the absorption film 70; and

[0094] The manufacturing process is performed by removing the resist pattern.

[0095] The absorption film 70 formed of a material containing tantalum (Ta) and nitrogen (N) may be etched by dry etching using a gas containing chlorine (Cl) or a gas containing fluorine (F).

[0096] Alternatively, a reflective mask can be created by including:

[0097] Preparing a reflective mask blank process;

[0098] If necessary, a step of forming a resist film 190 on the etching mask film 170;

[0099] A step of forming a resist pattern from the resist film 190 on the etching mask film 170;

[0100] The process of etching the etching mask film 170 by using the resist pattern as an etching mask to form a pattern of the etching mask film 170 (see Figure 5 );

[0101] The absorption film 70 is etched using the etching mask film 170 pattern as an etching mask to form a pattern of the absorption film 70 (see Figure 2 );

[0102] Removing the resist pattern step; and

[0103] The manufacturing is performed by removing the pattern of the etching mask film 170.

[0104] The etching mask film 170 is made into a film containing chromium (Cr). The etching mask film 170 is patterned by dry etching using a gas containing chlorine (Cl) and oxygen (O) to form a pattern of the etching mask film 170. The pattern of the etching mask film 170 is used as an etching mask. After the absorption film 70 is patterned, the etching mask film 170 can be removed by dry etching using a gas containing chlorine (Cl) and oxygen (O).

[0105] [Example]

[0106] Hereinafter, the present embodiment will be specifically described based on Examples and Comparative Examples, but the present embodiment is not limited to the following Examples.

[0107] [Example 1]

[0108] On the main surface of a 152 mm square, 6.35 mm thick low thermal expansion glass substrate (SiO2-TiO2 glass substrate), a molybdenum (Mo) target and a silicon (Si) target were used, and the two targets were placed opposite to the main surface of the substrate 10. While the substrate 10 was rotated, a multilayer reflective film 20 with a thickness of 284 nm was formed by DC pulse magnetron sputtering. The targets were mounted on a sputtering device that could mount two targets and discharge one or both targets simultaneously, and the substrate 10 was set.

[0109] First, while argon (Ar) gas is introduced into the chamber, power is applied to the silicon (Si) target to form a 4nm thick silicon (Si) layer, and the power application to the silicon (Si) target is stopped. Next, while argon (Ar) gas is introduced into the chamber, power is applied to the molybdenum (Mo) target to form a 3nm thick molybdenum (Mo) layer, and the power application to the molybdenum (Mo) target is stopped. The operation of forming these silicon (Si) layers and molybdenum (Mo) layers is set as one cycle, and the cycle is repeated 40 times. After the molybdenum (Mo) layer of the 40th cycle is formed, finally, a 3nm silicon (Si) layer is formed by the above method, and a 0.5nm molybdenum (Mo) layer is formed thereon to form a multilayer reflective film 20.

[0110] A target was mounted on another sputtering device, and after the multilayer reflective film 20 was formed, the substrate 10 on which the multilayer reflective film 20 was formed was placed from the sputtering device on which the multilayer reflective film 20 was formed, through a conveying path maintained in a vacuum state, without being taken out to the atmosphere. Next, a protective film 50 was formed on the multilayer reflective film 20 by DC pulse magnetron sputtering using a ruthenium (Ru) target, with the target and the main surface of the substrate 10 facing each other, while the substrate 10 was rotated. At this time, while argon gas was flowing in the chamber, power was applied to the ruthenium (Ru) target, and a film of 3.0 nm in thickness composed of Ru was formed.

[0111] Next, the substrate 10 on which the multilayer reflective film 20 and the protective film 50 were formed was subjected to heat treatment at 150° C. for 15 minutes in an air atmosphere using a hot plate type heating device to oxidize the surface of the protective film 50 .

[0112] The reflectance of the film obtained by the heat treatment at a wavelength of 193 nm to 248 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer (SolidSpec 3700, manufactured by Shimadzu Corporation).

[0113] Next, on the film after the heat treatment, a tantalum (Ta) target was used, and the target and the main surface of the substrate 10 were made to face each other, and the absorption film 70 was formed by DC pulse magnetron sputtering while the substrate 10 was rotated. At this time, while argon (Ar) and nitrogen (N) were circulated in the chamber, power was applied to the tantalum (Ta) target, and a TaN film with a thickness of 70nm was formed.

[0114] The reflectance of the obtained film at wavelengths of 193nm to 248nm was measured using the same ultraviolet-visible-near-infrared spectrophotometer as before. The reflectance contrast was calculated based on the reflectance before and after the formation of the absorption film 70. The result was 27.4% at a wavelength of 193nm and 30.6% at 248nm, which was sufficient contrast for the pattern inspection light.

[0115] Next, when the composition of the absorption film 70 was measured by an X-ray photoelectron spectroscopy (XPS) device (manufactured by Thermo Fisher SCIENTIFIC, K-Alpha), tantalum (Ta) accounted for 57 atomic % and nitrogen (N) accounted for 43 atomic % relative to the total of tantalum (Ta) and nitrogen (N). At this time, a surface oxide layer (thickness 1 nm) was formed due to natural oxidation in the atmosphere. The surface oxide layer oxygen content was 20 atomic % relative to the total of tantalum (Ta), nitrogen (N) and oxygen (O) on the side of the surface oxide layer farthest from the substrate 10.

[0116] [Example 2]

[0117] The multilayer reflective film 20 was formed in the same manner as in Example 1. On the multilayer reflective film 20, a protective film 50 was formed by DC pulse magnetron sputtering using a ruthenium (Ru) target and a niobium (Nb) target with the two targets facing the main surface of the substrate 10 while the substrate 10 was rotated.

[0118] Specifically, each target was mounted on another sputtering device capable of mounting two targets and simultaneously discharging one or both targets, and after the multilayer reflective film 20 was formed, the multilayer reflective film 20 was not taken out to the atmosphere, and the substrate 10 on which the multilayer reflective film 20 was formed was set from the sputtering device on which the multilayer reflective film 20 was formed through a conveying path maintained in a vacuum state. Next, while argon gas was flowing in the chamber, power was simultaneously applied to the ruthenium (Ru) target and the niobium (Nb) target, and a film having a thickness of 3.9 nm composed of RuNb with a composition ratio of 88 atomic % of ruthenium (Ru) and 12 atomic % of niobium (Nb) was formed as the protective film 50.

[0119] Then, heat treatment was performed at 150° C. for 15 minutes in the same manner as in Example 1, and then the reflectance at wavelengths of 193 nm to 248 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer.

[0120] In addition, on the protective film 50, as an absorption film 70, a film similar to that of Example 1 was formed, that is, a film in which tantalum (Ta) was 57 atomic % and nitrogen (N) was 43 atomic % relative to the total of tantalum (Ta) and nitrogen (N). The reflectivity at wavelengths of 193 nm to 248 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer. The reflectivity contrast was calculated based on the reflectivity before and after the absorption film 70 was formed. The result was 24.9% at a wavelength of 193 nm and 26.0% at a wavelength of 248 nm, which was sufficient contrast for the pattern inspection light.

[0121] [Example 3]

[0122] The multilayer reflective film 20 was formed in the same manner as in Example 1. On the multilayer reflective film 20, a ruthenium (Ru) target and a niobium (Nb) target were used, and the two targets and the main surface of the substrate 10 were opposed to each other, and the substrate 10 was rotated while the protective film 50 was formed by DC pulse magnetron sputtering. A film having a thickness of 3.6 nm composed of RuNb with a composition ratio of 85 atomic % of ruthenium (Ru) and 15 atomic % of niobium (Nb) was formed as the protective film 50 in the same manner as in Example 2, except that power was applied to each target when power was applied to the ruthenium (Ru) target and the niobium (Nb) target simultaneously.

[0123] Next, heat treatment was performed at 150° C. for 15 minutes in the same manner as in Example 1, and then the reflectance at wavelengths of 193 nm to 248 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer.

[0124] In addition, an absorption film 70 is formed on the protective film 50. At this time, except for changing the ratio of the argon (Ar) gas and the nitrogen (N) gas introduced into the chamber, the absorption film 70 with a thickness of 70 nm and 60 atomic % of tantalum (Ta) and 40 atomic % of nitrogen (N) is formed in the same manner as in Example 1. The absorption film 70 is naturally oxidized in the atmosphere to form a surface oxide layer (thickness 1 nm). The oxygen content of the surface oxide layer is 22 atomic % relative to the total of tantalum (Ta), nitrogen (N) and oxygen (O) on the side of the surface oxide layer farthest from the substrate 10.

[0125] Then, the reflectivity at wavelengths of 193nm to 248nm was measured using an ultraviolet-visible-near-infrared spectrophotometer. The reflectivity contrast was calculated based on the reflectivity before and after the formation of the absorption film 70. The result was 22.1% at a wavelength of 193nm and 27.3% at 248nm, which is sufficient contrast with the pattern inspection light.

[0126] [Example 4]

[0127] The multilayer reflective film 20 was formed in the same manner as in Example 1. On the multilayer reflective film 20, a ruthenium (Ru) target and a niobium (Nb) target were used, and the two targets and the main surface of the substrate 10 were opposed to each other, and the substrate 10 was rotated while the protective film 50 was formed by DC pulse magnetron sputtering. A film having a thickness of 3.9 nm composed of RuNb with a composition ratio of 82 atomic % of ruthenium (Ru) and 18 atomic % of niobium (Nb) was formed as the protective film 50 in the same manner as in Example 2, except that power was applied to each target when power was applied to the ruthenium (Ru) target and the niobium (Nb) target simultaneously.

[0128] Next, heat treatment was performed at 150° C. for 15 minutes in the same manner as in Example 1, and then the reflectance at wavelengths of 193 nm to 248 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer.

[0129] In addition, except that the ratio of argon (Ar) gas and nitrogen (N) gas introduced into the chamber as an absorption film 70 on the protective film 50 is changed, the absorption film 70 with a thickness of 70 nm, which absorbs tantalum (Ta) of 70 atomic % and nitrogen (N) of 30 atomic %, is naturally oxidized in the atmosphere to form a surface oxide layer (thickness 1.3 nm). The oxygen content of the surface oxide layer is 30 atomic % relative to the total of tantalum (Ta), nitrogen (N) and oxygen (O) on the side of the surface oxide layer farthest from the substrate 10.

[0130] Then, the reflectivity at wavelengths of 193nm to 248nm was measured using an ultraviolet-visible-near-infrared spectrophotometer. The reflectivity contrast was calculated based on the reflectivity before and after the formation of the absorption film 70. The result was 21.1% at a wavelength of 193nm and 28.0% at 248nm, which is sufficient contrast with the pattern inspection light.

[0131] [Example 5]

[0132] The multilayer reflective film 20 and the protective film 50 were formed in the same manner as in Example 3, and heat treated at 150° C. for 15 minutes in the same manner as in Example 1. Then, the reflectivity at wavelengths of 193 nm to 248 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer.

[0133] The absorption film 70 was formed in the same manner as in Example 1 except that the film thickness was 61 nm (57 atomic % of tantalum (Ta) and 43 atomic % of nitrogen (N) relative to the total of tantalum (Ta) and nitrogen (N), and then the reflectance at wavelengths of 193 nm to 248 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer. The reflectance contrast was calculated based on the reflectance before and after the absorption film 70 was formed, and the result was 22.5% at a wavelength of 193 nm and 26.5% at a wavelength of 248 nm, which was sufficient contrast for the pattern inspection light.

[0134] [Comparative Example 1]

[0135] The multilayer reflective film 20 and the protective film 50 were formed in the same manner as in Example 2, and heat treated at 150° C. for 15 minutes in the same manner as in Example 1. Then, the reflectivity at wavelengths of 193 nm to 248 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer.

[0136] Then, an absorption film 70 was formed. However, when forming the absorption film 70, nitrogen (N) gas was not introduced into the chamber, only argon (Ar) gas was introduced, and power was applied to the tantalum (Ta) target to form a Ta film with a thickness of 70 nm. The absorption film 70 was naturally oxidized in the atmosphere to form a surface oxide layer (thickness 1.5 nm). The oxygen content of the surface oxide layer was 50 atomic % relative to the total of tantalum (Ta), nitrogen (N) and oxygen (O) on the side of the surface oxide layer farthest from the substrate 10.

[0137] Then, the reflectance at wavelengths of 193nm to 248nm was measured using an ultraviolet-visible-near-infrared spectrophotometer. The reflectance contrast was calculated based on the reflectance before and after the absorption film 70 was formed. The result was 8.2% at a wavelength of 193nm and 17.1% at 248nm, which was not enough for the pattern inspection light.

[0138] [Comparative Example 2]

[0139] The multilayer reflective film 20 and the protective film 50 were formed in the same manner as in Example 2, and heat treated at 150° C. for 15 minutes in the same manner as in Example 1. Then, the reflectivity at wavelengths of 193 nm to 248 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer.

[0140] Next, an absorption film 70 was formed. When forming the absorption film 70, the same operation as in Example 1 was performed except that the ratio of the argon (Ar) gas and the nitrogen (N) gas introduced into the chamber was changed, and an absorption film 70 with a thickness of 70 nm and 80 atomic % of tantalum (Ta) and 20 atomic % of nitrogen (N) was formed. The absorption film 70 was naturally oxidized in the atmosphere to form a surface oxide layer (1.5 nm thick). The oxygen content of the surface oxide layer was 45 atomic % relative to the total of tantalum (Ta), nitrogen (N) and oxygen (O) on the side of the surface oxide layer farthest from the substrate 10.

[0141] Then, the reflectance at wavelengths of 193nm to 248nm was measured using an ultraviolet-visible-near-infrared spectrophotometer. The reflectance contrast was calculated based on the reflectance before and after the formation of the absorption film 70. The result was 17.0% at a wavelength of 193nm and 20.2% at 248nm, which was not enough for the pattern inspection light.

[0142] [Comparative Example 3]

[0143] The multilayer reflective film 20 and the protective film 50 were formed in the same manner as in Example 2, and heat treated at 150° C. for 15 minutes in the same manner as in Example 1. Then, the reflectivity at wavelengths of 193 nm to 248 nm was measured using an ultraviolet-visible-near-infrared spectrophotometer.

[0144] Next, an absorption film 70 was formed. At this time, as in Comparative Example 2, after forming a film with a thickness of 66 nm in which tantalum (Ta) was 80 atomic % and nitrogen (N) was 20 atomic %, argon (Ar) gas and oxygen (O) were introduced into the same chamber to form an oxide film with a thickness of 4 nm in which tantalum (Ta) was 40 atomic % and oxygen (O) was 60 atomic %, and the absorption film 70 with a total film thickness of 70 nm was formed.

[0145] Then, the reflectivity at wavelengths of 193nm to 248nm was measured using an ultraviolet-visible-near-infrared spectrophotometer. The reflectivity contrast was calculated based on the reflectivity before and after the formation of the absorption film 70. The result was 27.8% at a wavelength of 193nm and 39.8% at 248nm, which is sufficient contrast with the pattern inspection light.

[0146] On the other hand, since the oxide film is partially thick and has a high degree of oxidation, the etching rate during processing of the oxidized portion is slower than that of the non-oxidized portion, and there is a possibility that the cross-sectional shape of the pattern will deteriorate.

[0147] Explanation of symbols

[0148] 10 substrates

[0149] 20Reflective multilayer film

[0150] 50 protective film

[0151] 70 Absorption Film

[0152] 170 The mask film is etched.

Claims

1. A reflective mask blank for use as a raw material of a reflective mask used in EUV lithography using EUV light as exposure light, characterized in that: include: substrate; a multilayer reflective film formed on one main surface of the substrate and used for reflecting exposure light; A protective film formed in contact with the multilayer reflective film; as well as an absorbing film that absorbs exposure light formed on the protective film, wherein the protective film is formed of a film containing ruthenium (Ru), The absorption film is formed of a single layer film composed of tantalum (Ta) and nitrogen (N), wherein the content of nitrogen is greater than 30 atomic % and less than 60 atomic %. The contrast ratio between the reflected light on the surface of the protective film and the reflected light on the surface of the absorption film with respect to light having a wavelength of 193 nm to 248 nm is 20% or more.

2. The reflective mask blank according to claim 1, characterized in that: The absorption film has a thickness of 50 nm to 80 nm.

3. The reflective mask blank according to claim 1, characterized in that: The protective film is composed of ruthenium (Ru) or ruthenium (Ru) and niobium (Nb).

4. The reflective mask blank according to claim 1 or 2, characterized in that: The protective film has a thickness of 2 nm to 5 nm.

5. The reflective mask blank according to claim 1 or 2, characterized in that: Further including: An etching mask film containing Cr, wherein the Cr is used as an etching mask when processing the absorption film.

6. A method for manufacturing a reflective mask blank, characterized in that: The reflective mask blank according to claim 1 or 2 is produced by sputtering film formation.

7. The method for manufacturing a reflective mask blank according to claim 6, wherein: After the absorption film is formed on the surface on the side away from the substrate, an oxide layer with a film thickness of 2 nm or less is formed by exposing it to the air or performing a heat treatment at a temperature of 150° C. or less in the air atmosphere.

8. The method for manufacturing a reflective mask blank according to claim 6 or 7, characterized in that: The protective film is composed of ruthenium (Ru) or ruthenium (Ru) and niobium (Nb), and after the protective film is formed, heat treatment is performed at 150° C. or less in an air atmosphere.

Citation Information

Patent Citations

  • Reflective photomask

    JP2002122981A

  • Reflecting type exposure mask, its manufacturing method and semiconductor element

    JP2002246299A